Cover Feature: A Strategy of "Self‐Isolated Enhanced Emission" to Achieve Highly Emissive Dual‐State Emission for Organic Luminescent Materials (Chem. Eur. J. 41/2018). Issue 41 (11th July 2018) - Xu, Yanzi; Ren, Lin; Dang, Dongfeng; Zhi, Ying; Wang, Xiaochi; Meng, Lingjie
Abstract : A "self‐isolated enhanced emission" (SIEE) strategy through flexible alkyl chains is proposed to suppress and prevent the emission‐quenched π‐π stacking in aggregated solid states, leading to a highly emissive dual‐state emission in organic luminescent materials. More information can be found in the Full Paper by L. Meng, D. Dang, et al. onpage 10383 .